Religious coping as a protective factor against stress in medical education - Mastiti, Ridha Nur (Bulan Sabit Merah Indonesia, 2025)
College students often face the challenge of adjusting to various daily routines, which can create pressure and lead to negative emotional experiences. To navigate these difficulties, students must develop effective coping strategies that enhance their ability to manage stress. One approach that can support stress reduction is religious coping, as it provides a sense of comfort, guidance, and emotional stability. Additionally, resilience plays a crucial role in helping individuals overcome obstacles and persist through adversity. Coping mechanisms, including those rooted in spirituality, are essential for maintaining emotional well-being and fostering strong resilience in the face of academic and personal challenges. This cross-sectional observational analytic study gathered primary data using two questionnaire instruments: BRIEF RCOPE and Growth-Focused Resilience. Samples were collected through non-random sampling from 174 students of the Faculty of Medicine, Universitas Lambung Mangkurat, class of 2023. Data analysis was conducted using the Chi-Square Test with SPSS version 21. The obtained p-value (sig) was 0.000 (0.05), indicating a significant relationship between religious coping and resilience. Religious coping was identified as a factor influencing resilience, where effective coping strategies contribute to positive personal growth, while ineffective coping may hinder resilience development. The study concludes that there is a significant correlation between religious coping and resilience among students of the Faculty of Medicine, Universitas Lambung Mangkurat, class of 2023.